1986
DOI: 10.1111/j.1348-0421.1986.tb03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Split‐Product Trivalent A(H1N1), A(H3N2), and B Influenza Vaccines

Abstract: The reactogenicity and immunogenicity of Tween-ether split trivalent A(H1N1), A (H3N2), and B influenza vaccine in primary school children aged seven to 12 years, and the persistence of antibodies following two doses of vaccine were studied during 1980-1984. Adverse reactions were infrequent, and, even when reported, were chiefly local ones, mild in nature and of short duration. Most of the reactions were less frequent after the second dose than after the first dose. Most of the systemic reactions occurred dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…The rate of seroprotection against the B strain in the steroid-treated group was below 70%, but there was no statistically significant difference (Table 3). This result is similar to reports that the antibody response against the B strain in the steroid-treated group is lower than that in the non-steroid-treated group (32)(33)(34) but is in contrast to the research of Park et al indicating that the antibody response against the B strain in asthmatic patients who receive steroid treatment is higher (25).…”
Section: Discussioncontrasting
confidence: 56%
“…The rate of seroprotection against the B strain in the steroid-treated group was below 70%, but there was no statistically significant difference (Table 3). This result is similar to reports that the antibody response against the B strain in the steroid-treated group is lower than that in the non-steroid-treated group (32)(33)(34) but is in contrast to the research of Park et al indicating that the antibody response against the B strain in asthmatic patients who receive steroid treatment is higher (25).…”
Section: Discussioncontrasting
confidence: 56%
“…Substantial antibody titers decay within 4–8 months post-vaccination [46],[47], combined with rapid antigenic drift in circulating viruses [48], require vaccination campaigns to be initiated a few weeks prior to the onset of local influenza activity. A practical outcome of our study was to define three broad influenza regions on the basis of epidemiological data (Figure 6B), which have distinct influenza seasonality characteristics and broadly align with climatic zones.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody levels induced by vaccine decline after vaccination ( 3 5 ). Although a 2008 literature review found no clear evidence of more rapid decline among older adults ( 6 ), a 2010 study noted a statistically significant decline in antibody titers 6 months after vaccination among persons aged ≥65 years ( 5 ).…”
Section: Groups Recommended For Vaccination and Timing Of Vaccinationmentioning
confidence: 99%